PENGARUH OUTBOUND TERHADAP TINGKAT KEPERCAYAAN DIRI SISWA KELAS VII DI SMPN 4 PEKANBARU T.P 2016/2017 - Siti Ruzliana; Rosmawati '; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The aim of this research is to know the effect of outbound on student self confidence level of the first grade student of SMPN 4 pekanbaru year 2016/2017. This research was conducted at SMPN 4 Pekanbaru from March 2 until May 2017. The method of this research used true-experimental design with pre test-post test control group desin pattern. The subject of this research was the first grade student of SMPN 4 Pekanbaru who have low confidence. The instrument of data collection used is questionnaire which likert scale. The data analysis technique were used is quantitative data analysis that is used statistc. Based on the result of t test of correlated sample, there were significant different to the self confidence level of students before and after given outbound, the result of calculation obtained that thitung -16.916 < ttabel -2.052. Furthermore, the result of t test sample calculation is not correlated obtained thitung -8.984 < ttabel -2,005, if it is compared between experimental group and control group there was significant difference of outbound implementation toward student confidence level.Key Words : Outbound, Level of Self Confidence.